Cathode material, cathode and lithium secondary battery containing same
The bimodal positive electrode material with optimized cation mixing and particle size ratios addresses the durability and high-temperature life issues in lithium secondary batteries, resulting in improved performance and lifespan.
Patent Information
- Application Number
- JP2024554697
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-03-28
- Filing Date
- 2023-03-29
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-03-29
AI Technical Summary
Lithium secondary batteries face challenges with the durability and high-temperature life of positive electrode materials, particularly due to particle cracking and structural instability caused by the anisotropic volume change of nickel in high nickel content materials.
A bimodal type positive electrode material is developed, with a specific ratio of cation mixing between large and small particle-sized active materials, and optimized primary particle sizes to enhance durability and high-temperature performance.
The positive electrode material exhibits improved durability and high-temperature life characteristics by reducing particle cracking and surface deterioration, leading to enhanced lifespan and performance of lithium secondary batteries.
Smart Images

Figure 2025509530000001 
Figure 2025509530000002 
Figure 2025509530000003
Abstract
Description
[Technical field]
[0001] [CROSS REFERENCE TO RELATED APPLICATIONS] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0039234 filed on March 29, 2022 and Korean Patent Application No. 10-2023-0040836 filed on March 28, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.
[0002] The present invention relates to a cathode material, a cathode and a lithium secondary battery including the same, and more particularly to a cathode material having improved durability and high-temperature life by adjusting the ratio of cation mixing rates and the ratio of primary particle sizes between two cathode active materials having different particle sizes, and a cathode and a lithium secondary battery including the same. [Background technology]
[0003] A lithium secondary battery generally comprises a positive electrode, a negative electrode, a separator, and an electrolyte. The positive electrode and the negative electrode contain active materials capable of intercalating and deintercalating lithium ions.
[0004] Lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2, LiMnO4, etc.), lithium iron phosphate compound (LiFePO4), etc. have been used as positive electrode active materials for lithium secondary batteries. Among these, lithium cobalt oxide has the advantages of high operating voltage and excellent capacity characteristics, but the cost of the raw material cobalt is high and the supply is unstable, making it difficult to commercially apply it to large-capacity batteries. On the other hand, lithium nickel oxide has the disadvantage of being difficult to realize sufficient life characteristics due to poor structural stability, while lithium manganese oxide has excellent stability but poor capacity characteristics. To compensate for this, lithium composite transition metal oxides containing two or more transition metals have been developed, and among them, lithium nickel cobalt manganese oxide is widely used.
[0005] Generally, lithium nickel cobalt manganese oxide is in the form of spherical secondary particles formed by agglomeration of tens to hundreds of primary particles, and thus not only is it prone to particle cracking as the primary particles fall off during the rolling process when manufacturing the positive electrode, but there are also problems with cracks occurring along the interface between the primary particles as the volume of the unit lattice changes due to the insertion and extraction of lithium ions during repeated charging and discharging. When particle cracking or cracks occur in the positive electrode active material, the contact area with the electrolyte increases, which increases the generation of gas due to side reactions with the electrolyte and the deterioration of the active material, which can result in reduced life characteristics.
[0006] Furthermore, in order to realize a high energy density, recent attempts have been actively made to increase the nickel content in the lithium nickel cobalt manganese oxide. However, in this case, the high reactivity and anisotropic volume change of nickel increases the possibility of intraparticle cracks occurring during charging and discharging, which may cause the structure to collapse and degrade the performance of the battery.
[0007] Therefore, there is a need to develop a high-nickel positive electrode material that has excellent structural stability and also exhibits high energy density. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 10-2021-0031325 Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention aims to provide a bimodal cathode material for lithium secondary batteries that has less cracking and improved surface durability by controlling the ratio of cation mixing rates between large and small particles and the ratio of primary particle sizes within optimal ranges.
[0010] The present invention also aims to provide a positive electrode and a lithium secondary battery having improved high-temperature life by applying the above-mentioned positive electrode material. [Means for solving the problem]
[0011] According to one embodiment, the present invention includes a large particle size positive electrode active material and a small particle size positive electrode active material, When the cation mixing ratio of the large particle diameter positive electrode active material is Ml and the cation mixing ratio of the small particle diameter positive electrode active material is Ms, Ml / Ms is 0.6 to 4.0, The present invention provides a positive electrode material for lithium secondary batteries in which Pl / Ps is 0.1 to 2.0, where Pl is the average particle size of the primary particles of the large particle size positive electrode active material and Ps is the average particle size of the primary particles of the small particle size positive electrode active material.
[0012] The present invention also provides a positive electrode including the positive electrode material for lithium secondary batteries, and a lithium secondary battery including the positive electrode. Effect of the Invention
[0013] The cathode material for lithium secondary batteries according to the present invention exhibits excellent durability by controlling the ratio of the cation mixing rate between the large particle diameter cathode active material and the small particle diameter cathode active material and the ratio of the average particle diameter of the primary particles within an optimal range, and therefore, a lithium secondary battery using the cathode material of the present invention has excellent life characteristics at high temperatures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The present invention will now be described in more detail.
[0015] In the present invention, the term "single particle" refers to a particle consisting of one single primary particle. In the present invention, the term "primary particle" refers to a particle unit which may be a single crystal lacking a crystalline grain boundary, or a polycrystal having no grain boundary in appearance when observed at a magnification of 5,000 to 20,000 times using a scanning electron microscope (SEM). In the present invention, the term "quasi-single particle" refers to a particle which is a complex formed of about 30 or less primary particles.
[0016] In the present invention, the term "primary particle" refers to a particle unit having no grain boundary when observed at a magnification of 5,000 to 20,000 times using a scanning electron microscope, and the term "secondary particle" refers to a particle formed by agglomeration of tens to hundreds of primary particles, and specifically, the secondary particle may be an agglomeration of more than about 30 primary particles.
[0017] In the present invention, the "average particle size of primary particles" refers to the arithmetic mean value calculated after measuring the particle sizes of at least 20 primary particles observed in a scanning electron microscope image. In this case, the particle size refers to the longest axis diameter of the primary particles.
[0018] In the present invention, the "D50 of the positive electrode active material" means a particle size corresponding to 50% of the volume cumulative in the volume cumulative particle size distribution of the positive electrode active material powder, and may be measured using a laser diffraction method. For example, the positive electrode active material powder is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., S-3500 by Microtrac), and ultrasonic waves of about 28 kHz are irradiated at an output of 60 W, and a graph of the volume cumulative particle size distribution is obtained, and the particle size at the point where the volume cumulative amount is 50% is obtained from the obtained volume cumulative particle size distribution graph.
[0019] The "specific surface area" in the present invention is measured by the BET method, and specifically, may be calculated from a nitrogen adsorption isotherm obtained under a liquid nitrogen atmosphere at 77K using a BELSORP-MAX (MicrotracBEL corp.).
[0020] In the present invention, the "cation mixing ratio" refers to the ratio of nickel ions (Ni ions) to the total amount of lithium sites (Li sites) in the lithium layer of the lithium nickel oxide having a layered structure. 2+ ) is mixed in and occupies a certain percentage, and is a value measured through X-ray diffraction analysis (XRD).
[0021] Specifically, the X-ray diffraction analysis may be performed as follows. A Bruker D8 Endeavor (Cu Kα, λ=1.54 Å) equipped with a LynxEye XE-T position sensitive detector was used to measure the diffraction pattern of the sample, setting FDS 0.5°, 2θ (theta) 15° to 90°, step size 0.02°, and total scan time about 20 minutes. Rietveld refinement was performed on the measured data, taking into account the charge at each site (metal at the transition metal site is +3, Ni at the Li site is +2) and cation mixing. Instrumental broadening during analysis was considered using the Fundamental Parameter Approach (FPA) provided by the Bruker TOPAS program, and all peaks in the measurement range were used during fitting. Peak shapes are fitted using only the Lorentzian contribution as FP (First Principle) type available in TOPAS, without considering strain. The Ni excess value identified after Rietveld refinement is defined as the cation mixing ratio.
[0022] Cathode material The cathode material according to the present invention includes a large particle size cathode active material having a relatively large particle size and a small particle size cathode active material having a relatively small particle size, specifically, has a bimodal particle size distribution. In this case, the small particle size cathode active material fills the voids of the large particle size cathode active material during rolling of the electrode, thereby increasing the electrode density and realizing a high energy density.
[0023] However, when a large particle size positive active material and a small particle size positive active material are mixed to form an electrode, the small particle size positive active material located between the large particle size particles plays a role in alleviating direct contact between the large particle size particles, so that the small particle size positive active material is relatively subjected to more physical stress, which may cause particle cracking to deepen. In addition, a positive active material with a high nickel content has a higher degree of anisotropic contraction and expansion during charging and discharging compared to a positive active material with a low nickel content, which increases the possibility of intra-particle cracking, and the cracks that have developed on the surface induce the penetration of electrolyte, which causes structural deterioration of the positive electrode material, which may shorten the life of the battery.
[0024] In order to solve this problem, the inventors adjusted the ratio of the cation mixing ratio (Ml) of the large particle diameter positive active material to the cation mixing ratio (Ms) of the small particle diameter positive active material, Ml / Ms, from 0.6 to 4.0, and suppressed the acceleration of overall deterioration of the positive electrode by lowering the cation mixing ratio of the small particle diameter, which is prone to severe particle cracking. Specifically, since the cation mixing of the active material is likely to mainly occur on the surface, which has relatively high interfacial energy and is unstable, rather than inside the primary particles, a chain reaction of ion exchange reactions occurs around the site where the cation mixing occurs during charging and discharging, which tends to propagate the collapse of the structure, which affects the generation and propagation of microcracks.
[0025] If the Ml / Ms ratio is less than 0.6, there is a problem that the deterioration caused by the surface condition of small particles is accelerated as described above, and if it exceeds 4.0, it is undesirable in that the deterioration is accelerated when microcracks occur in large particles. Specifically, the Ml / Ms ratio may be 0.8 to 3.5, and more specifically, 1.0 to 3.0.
[0026] Meanwhile, the cation mixing ratio (Ml) of the large particle size positive electrode active material may be 1.0 at% to 2.0 at%, more preferably 1.2 at% to 1.5 at%. When the cation mixing ratio (Ml) of the large particle size positive electrode active material satisfies the above range, it is preferable in that the generation of microcracks in the large particle size positive electrode active material during the operation of the battery can be prevented to the greatest extent possible, and the durability can be improved, thereby improving the lifespan. Here, at% means atomic%.
[0027] The small particle size positive electrode active material may have a cation mixing ratio (Ms) of 0.5 at% to 1.5 at%, more preferably 0.8 at% to 1.3 at%. When the cation mixing ratio (Ms) of the small particle size positive electrode active material satisfies the above range, it is preferable in that deterioration due to particle cracking of the small particle size positive electrode active material can be suppressed.
[0028] In addition, the present inventors adjusted the average particle size (Pl) of the primary particles of the large particle diameter positive active material and the average particle size (Ps) of the primary particles of the small particle diameter positive active material, Pl / Ps, to 0.1 to 2.0. If the Pl / Ps is less than 0.1 or exceeds 2.0, it means that the particle strength of the large particles or small particles is not good, and the amount of fine powder generated increases as the particle cracks of the small particle diameter increase during the rolling process of the electrode, and the area of side reactions also increases, which is undesirable in that the deterioration of the battery is accelerated and the high temperature life and output characteristics are deteriorated. Specifically, the Pl / Ps may be 0.1 to 1.5, more specifically, 0.3 to 1.0.
[0029] In other words, adjusting Ml / Ms and Pl / Ps within the above ranges suppresses particle cracking of the large particle size positive electrode active material and suppresses surface deterioration of the small particle size positive electrode active material, thereby improving the durability of the positive electrode material and ultimately improving the life of the battery.
[0030] In one embodiment of the present invention, the large particle diameter positive electrode active material may have a D50 of 8 μm to 18 μm, preferably 10 μm to 18 μm, more preferably 10 μm to 15 μm. The small particle diameter positive electrode active material may have a D50 of 2 μm to 7 μm, preferably 3 μm to 6 μm, more preferably 4 μm to 6 μm. When the D50 of the large particle diameter positive electrode active material and the D50 of the small particle diameter positive electrode active material satisfy the above range, it is preferable in that the electrode rolling characteristics can be maximized.
[0031] Meanwhile, the large particle size positive electrode active material and the small particle size positive electrode active material may each independently be composed of a single particle; a similar-single particle; a secondary particle formed by agglomeration of a number of primary particles; or a combination thereof. Specifically, the large particle size positive electrode active material may be composed of secondary particles, and the small particle size positive electrode active material may be composed of a single particle and / or a similar-single particle. In this case, cracking and deterioration of the small particles can be suppressed, and the rolling characteristics of the electrode can be improved.
[0032] The average particle size (Pl) of the primary particles of the large particle size positive active material may be 0.2 μm to 1.0 μm, more preferably 0.2 μm to 0.8 μm. When the average particle size (Pl) of the primary particles of the large particle size positive active material satisfies the above range, it is preferable in that particle cracking is minimized.
[0033] The average particle size (Ps) of the primary particles of the small particle size positive electrode active material may be 0.5 μm to 2.5 μm, preferably 0.5 μm to 2.0 μm, more preferably 0.8 μm to 2.0 μm. When the average particle size (Ps) of the primary particles of the small particle size positive electrode active material satisfies the above range, it is preferable in terms of suppressing cracking of the small particles and suppressing side reactions.
[0034] In one embodiment of the present invention, the specific surface area of the large particle diameter positive active material is Bl, and the specific surface area of the small particle diameter positive active material is Bs, and Bl / Bs may be 0.15 to 1.6, preferably 0.3 to 1.6, and more preferably 0.5 to 1.5. The larger the specific surface area of the positive active material, the larger the surface area that can participate in the charge / discharge reaction, and therefore the output characteristics can be improved, but this also means that the surface area that deteriorates increases, so it is important to adjust the specific surface area to an appropriate level. Considering that the surface area per unit weight of small particles is larger than that of large particles, it is preferable to adjust Bl / Bs within the above range in the case of the positive electrode material according to the present invention.
[0035] Specifically, the specific surface area of the large particle diameter positive electrode active material is 0.2 m 2 / g to 1.0m 2 / g, preferably 0.4m 2 / g to 0.8m 2 / g, more preferably 0.6m 2 / g to 0.8m 2 / g, and the specific surface area of the small particle diameter positive electrode active material may be 0.5 m 2 / g to 1.2m 2 / g, preferably 0.5m 2 / g to 1.0m 2 / g, more preferably 0.6m 2 / g to 1.0m 2 / g.
[0036] Specifically, the large particle size positive active material and the small particle size positive active material may each include a lithium nickel-based oxide containing nickel, cobalt, and manganese.
[0037] In one embodiment of the present invention, the large particle size positive electrode active material and the small particle size positive electrode active material each may contain a lithium nickel-based oxide in which the molar ratio of nickel among transition metals is 70 mol % or more, more preferably 80 mol % or more.
[0038] On the one hand, the large-particle-size positive electrode active material and the small-particle-size positive electrode active material can each contain a lithium nickel-based oxide represented by the following Chemical Formula 1, and the lithium nickel-based oxide contained in the large-particle-size positive electrode active material and the lithium nickel-based oxide contained in the small-particle-size positive electrode active material may be the same as or different from each other.
[0039] [Chemical Formula 1] Li 1+x (Ni a Co b Mn c M d )O 2-y In the Chemical Formula 1, M is one or more selected from the group consisting of Al, Mg, V, Ti, Zr, Nb, and W, x, a, b, c, and d are -0.10 ≦ x ≦ 0.20, 0.50 ≦ a < 1.0, 0 < b ≦ 0.40, 0 < c ≦ 0.30, 0 ≦ d ≦ 0.10, a + b + c + d = 1, and 0 ≦ y ≦ 0.05, respectively.
[0040] The 1 + x indicates the molar ratio of lithium in the lithium nickel-based oxide, and may be -0.1 ≦ x ≦ 0.2 or 0 ≦ x ≦ 0.2. When the molar ratio of lithium satisfies the above range, the crystal structure of the lithium nickel-based oxide can be stably formed.
[0041] The a indicates the molar ratio of nickel among all the metals excluding lithium in the lithium nickel-based oxide, and may be 0.60 ≦ a < 1, 0.70 ≦ a < 1, or 0.85 ≦ a < 1. When the molar ratio of nickel satisfies the above range, a high energy density is shown, so that a high capacity can be realized.
[0042] The b indicates the molar ratio of cobalt among all the metals excluding lithium in the lithium nickel-based oxide, and may be 0 < b ≦ 0.30, 0 < b ≦ 0.20, or 0 < b ≦ 0.10. When the molar ratio of cobalt satisfies the above range, good resistance characteristics and output characteristics can be realized.
[0043] The c represents the molar ratio of manganese among the total metals excluding lithium in the lithium nickel-based oxide, and may be 0 < c ≤ 0.25, 0 < c ≤ 0.20, or 0 < c ≤ 0.10. When the molar ratio of manganese satisfies the above range, the structural stability of the positive electrode active material is excellently exhibited.
[0044] In one embodiment of the present invention, the large particle size positive electrode active material may contain one or more doping elements selected from the group consisting of Al, Mg, V, Ti, Zr, Nb, and W. In this case, there is an effect of suppressing structural deterioration and improving high temperature durability. Preferably, the large particle size positive electrode active material may contain Al as a doping element. That is, the d representing the molar ratio of the doping element among the total metals excluding lithium in the lithium nickel-based oxide may be 0 < d ≤ 0.08, 0 < d ≤ 0.06, or 0 < d ≤ 0.05.
[0045] In one embodiment of the present invention, the molar ratio of nickel among the transition metals in the lithium nickel-based oxide may be 70 mol% or more, and more preferably 80 mol% or more.
[0046] On the other hand, the lithium nickel-based oxide contained in the large particle size positive electrode active material may have a higher molar ratio of nickel among the transition metals than the lithium nickel-based oxide contained in the small particle size positive electrode active material. In this case, there is an advantage that the Ni composition of small particles with a large reaction area and relatively severe particle cracking can be set relatively low, thereby suppressing the deterioration of the positive electrode scale.
[0047] Meanwhile, the large particle diameter positive electrode active material and the small particle diameter positive electrode active material according to the present invention may further include a coating layer on the surface of the lithium nickel-based oxide particles, if necessary. In this case, the coating layer may include at least one coating element selected from the group consisting of Al, Ti, W, B, F, P, Mg, Ni, Co, Fe, Cr, V, Cu, Ca, Zn, Zr, Nb, Mn, Sr, Sb, Bi, Si, and S. When a coating layer is present on the surface of the lithium nickel-based oxide, the coating layer reduces the contact between the electrolyte and the lithium nickel-based oxide, thereby reducing the elution of transition metals and the generation of gas due to side reactions with the electrolyte. Preferably, the coating layer may include B, Co, Al, or a combination thereof, and more preferably, may include Co. When the coating layer includes Co, it is possible to obtain the effects of suppressing side reactions with the electrolyte, as well as improving output and reducing resistance.
[0048] Meanwhile, the positive electrode material may include a large particle diameter positive active material and a small particle diameter positive active material in a weight ratio of 50:50 to 90:10, preferably 50:50 to 80:20. When the weight ratio of the large particle diameter positive active material and the small particle diameter positive active material is within the above range, the small particles may be arranged between the large particles while minimizing space loss. This is preferable in that the packing density is optimized and it is advantageous for dispersing stress applied between the active materials during rolling, which is advantageous for improving the rolling characteristics of the electrode and realizing high energy.
[0049] positive electrode Next, the positive electrode according to the present invention will be described.
[0050] The positive electrode according to the present invention includes the positive electrode material according to the present invention. Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, and the positive electrode active material layer includes the positive electrode material according to the present invention.
[0051] Since the cathode material has been described above, a detailed description thereof will be omitted, and only the remaining components will be described below.
[0052] The positive electrode current collector may include a metal having high conductivity, and may be easily attached to the positive electrode active material layer, and may be non-reactive in the voltage range of the battery. The positive electrode current collector may be, for example, stainless steel, aluminum, nickel, titanium, calcined carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. The positive electrode current collector may have a thickness of typically 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, the positive electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0053] The positive electrode active material layer may optionally contain a conductive material and a binder in addition to the positive electrode material, as required.
[0054] At this time, the positive electrode material may be included in a content of 80 to 99 wt %, more specifically, 85 to 98.5 wt %, based on the total weight of the positive electrode active material layer, and excellent capacity characteristics can be exhibited when included in this content range.
[0055] The conductive material is used to give conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery. Specific examples include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; carbon-based materials such as carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive tubes such as carbon nanotubes; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these may be used alone or in combination. The conductive material may be included in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.
[0056] The binder plays a role in improving the adhesion between the positive electrode particles and between the positive electrode and the current collector. Specific examples of the binder include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and polymers in which hydrogen is replaced by Li, Na, or Ca, or various copolymers thereof, and one or more of these may be used alone or in combination. The binder may be included in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.
[0057] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode material. Specifically, the positive electrode may be manufactured by applying a positive electrode mixture, which is prepared by dissolving or dispersing the positive electrode material and, optionally, a binder, a conductive material, and a dispersant in a solvent, onto a positive electrode current collector, followed by drying and rolling, or by casting the positive electrode mixture onto a separate support, peeling it off from the support, and laminating the resulting film onto a positive electrode current collector.
[0058] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), dimethyl formamide (DMF), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, binder, and dispersant in consideration of the coating thickness of the slurry and the manufacturing yield, and to have a viscosity that can show excellent thickness uniformity when applied to manufacture a positive electrode.
[0059] Lithium secondary battery Next, the lithium secondary battery according to the present invention will be described.
[0060] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Since the positive electrode is the same as that described above, detailed description thereof will be omitted, and only the remaining components will be described in detail below.
[0061] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly including the positive electrode, the negative electrode, and a separator, and a sealing member that seals the battery container.
[0062] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.
[0063] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of typically 3 μm to 500 μm, and may be formed with fine irregularities on the surface of the current collector to enhance the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0064] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.
[0065] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium, such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. Also, a metallic lithium thin film may be used as the negative electrode active material. The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer.
[0066] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and is usually added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.
[0067] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10 wt % or less, preferably 5 wt % or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and examples of the conductive material include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; carbon fluoride; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.
[0068] The negative electrode active material layer may be prepared by coating a negative electrode mixture prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material in a solvent, on a negative electrode current collector and drying the coating. Alternatively, the negative electrode mixture may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.
[0069] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a passage for lithium ions to move. Any separator generally used in lithium secondary batteries may be used without any particular limitation. In particular, a separator having low resistance to ion movement of the electrolyte and excellent moisture-absorbing ability of the electrolyte solution is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high-melting point glass fiber, a polyethylene terephthalate fiber, or the like may be used. In addition, a coated separator containing a ceramic component or a polymeric material may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.
[0070] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.
[0071] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0072] The organic solvent may be used without any particular limitation as long as it can act as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester-based solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether-based solvent such as dibutyl ether or tetrahydrofuran; a ketone-based solvent such as cyclohexanone; an aromatic hydrocarbon-based solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvent that may be used include carbonate-based solvents such as polycarbonate (PC) and polycarbonate-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a hydrocarbon group having a linear, branched or cyclic structure with 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can enhance the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred.
[0073] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in lithium secondary batteries. Specifically, the anion of the lithium salt may be F - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - The lithium salt may be at least one selected from the group consisting of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably within the range of 0.1 to 4.0M. If the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that it can exhibit excellent electrolyte performance and lithium ions can move effectively.
[0074] In addition to the components of the electrolyte, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, water, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in the capacity of the battery, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5 wt % based on the total weight of the electrolyte.
[0075] As described above, the lithium secondary battery including the cathode material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).
[0076] According to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.
[0077] The battery module or the battery pack may be used as a power source for one or more medium- to large-sized devices including a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.
[0078] The external shape of the lithium secondary battery of the present invention is not particularly limited, but may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0079] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a large number of battery cells.
[0080] Examples of the medium- to large-sized devices include, but are not limited to, electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0081] The present invention will now be described in more detail with reference to specific examples.
[0082] <Production Example: Production of Positive Electrode Active Material> (1) Production Example 1 - Production of large particle size active material (production of positive electrode active materials A to E) Ni 0.90 Co 0.05 Mn 0.05 (OH)2, LiOH, and Al(OH)3 were added to a Henschel mixer (700L) in a molar ratio of (Ni+Co+Mn):Li:Al of 1:1.05:0.03 and mixed for 20 minutes at 400 rpm in the center. The mixed powder was placed in an alumina crucible measuring 330mm x 330mm and heat-treated (fired) for 15 hours at 750℃ in an oxygen (O2) atmosphere. The heat-treated active material was mixed with deionized water (Di-water) in a weight ratio of 50:50, stirred for 10 minutes, washed with water, and dried in a drying oven at 120℃ for 12 hours. Then, 0.1wt% of H3BO3 based on the total weight of the active material was mixed with the dried active material and heat-treated at 300℃ for 10 hours to produce large particle size positive active material A.
[0083] Positive electrode active materials B to E were prepared in the same manner as the positive electrode active material A, except that the molar ratio of Li and Al and the sintering temperature were changed as shown in Table 1 below.
[0084] [Table 1]
[0085] (2) Production Example 2 - Production of small particle size active material (production of positive electrode active materials F to J) Ni 0.88 Co 0.06 Mn 0.06 (OH)2 and LiOH were added to a Henschel mixer (700L) in a molar ratio of (Ni+Co+Mn):Li:Al of 1:1.05:0.03 and mixed for 20 minutes at 400 rpm in the center. The mixed powder was placed in an alumina crucible measuring 330mm x 330mm and heat-treated (fired) for 15 hours at 790℃ in an oxygen (O2) atmosphere. The heat-treated active material was mixed with deionized water (Di-water) in a weight ratio of 50:50, stirred for 10 minutes, washed with water, and dried in a drying oven at 120℃ for 12 hours. Then, the dried active material was mixed with 0.1wt% H3BO3 based on the total weight of the active material, and heat-treated at 300℃ for 10 hours to produce small particle size positive active material F.
[0086] Positive electrode active materials G to K were prepared in the same manner as the positive electrode active material F, except that the molar ratio of Li and Al and the sintering temperature were changed as shown in Table 2 below.
[0087] [Table 2]
[0088] (3) Measurement of the physical properties of the positive electrode active material For each of the positive electrode active materials prepared in Preparation Examples 1 and 2, the cation mixing ratio, the average primary particle diameter, D50, and the specific surface area were measured by the following methods, and the results are shown in Table 3 below.
[0089] Cation Mixture Ratio Diffraction patterns of the samples were measured using a Bruker D8 Endeavor (Cu Kα, λ = 1.54 Å) equipped with a LynxEye XE-T position sensitive detector, with FDS 0.5°, a step size of 0.02° in the 2θ (theta) range of 15° to 90°, and a total scan time of approximately 20 min. Rietveld refinement was performed on the measured data, taking into account the charge at each site (metals at transition metal sites are +3, Ni at Li sites is +2) and cation mixing. Instrumental broadening during analysis was considered using the Fundamental Parameter Approach (FPA) provided by the Bruker TOPAS program, and all peaks in the measurement range were used during fitting. Peak shapes were fitted using only the Lorentzian contribution in FP (First Principle) of the types available in TOPAS, without considering strain. The excess value of Ni identified after Rietveld refinement was defined as the cation mixing ratio.
[0090] Average primary particle size A cross-sectional image of each of the positive electrode active materials was observed using a scanning electron microscope, and the longest axis diameters of 20 primary particles in the cross section of the positive electrode active material were measured, and then the arithmetic average value was calculated.
[0091] D50 0.05 g of powder of each positive electrode active material was placed in a particle size distribution confirmation device (Microtrac, MTS-3500) and irradiated with ultrasonic waves of about 28 kHz at an output of 60 W to obtain a volume cumulative particle size distribution graph, and the particle size at the point where the volume cumulative amount was 50% was obtained on the obtained volume cumulative particle size distribution graph.
[0092] specific surface area 3 g of each positive electrode active material powder was placed in a BELSORP-MAX (MicrotracBEL corp.) to obtain a nitrogen adsorption isotherm under a liquid nitrogen atmosphere at 77 K, and the BET specific surface area was calculated using the isotherm.
[0093] [Table 3]
[0094] <Examples and Comparative Examples: Production of Cathode Material> Example 1. The positive electrode active material A produced in Production Example 1 and the positive electrode active material F produced in Production Example 2 were mixed in a weight ratio of 80:20 to produce a positive electrode material.
[0095] Example 2. The positive electrode active material B produced in Production Example 1 and the positive electrode active material G produced in Production Example 2 were mixed in a weight ratio of 80:20 to produce a positive electrode material.
[0096] Example 3. The positive electrode active material A produced in Production Example 1 and the positive electrode active material G produced in Production Example 2 were mixed in a weight ratio of 80:20 to produce a positive electrode material.
[0097] Example 4. The positive electrode active material A produced in Production Example 1 and the positive electrode active material F produced in Production Example 2 were mixed in a weight ratio of 50:50 to produce a positive electrode material.
[0098] Comparative Example 1 The positive electrode active material C produced in Production Example 1 and the positive electrode active material H produced in Production Example 2 were mixed in a weight ratio of 80:20 to produce a positive electrode material.
[0099] Comparative Example 2 The positive electrode active material D produced in Production Example 1 and the positive electrode active material I produced in Production Example 2 were mixed in a weight ratio of 80:20 to produce a positive electrode material.
[0100] Comparative Example 3. The positive electrode active material E produced in Production Example 1 and the positive electrode active material J produced in Production Example 2 were mixed in a weight ratio of 80:20 to produce a positive electrode material.
[0101] Comparative Example 4. The positive electrode active material D produced in Production Example 1 and the positive electrode active material G produced in Production Example 2 were mixed in a weight ratio of 80:20 to produce a positive electrode material.
[0102] Comparative Example 5. The positive electrode active material C produced in Production Example 1 and the positive electrode active material K produced in Production Example 2 were mixed in a weight ratio of 80:20 to produce a positive electrode material.
[0103] <Experimental Example> Experimental Example 1 - Fine powder generation rate 3 g of each of the cathode material powders prepared in Examples 1 to 4 and Comparative Examples 1 to 5 was placed in a cylindrical metal mold with a diameter of 2 cm and pressed under a pressure of 6 tons, and the volume cumulative particle size distribution was measured to determine the fine powder generation rate of less than 1 μm. The particle size distribution was measured using a Microtrac S-3500, and the fine powder generation rate of less than 1 μm was calculated based on the total weight of the cathode material, and then converted into volume %. The measurement results are shown in Table 4 below.
[0104] Experimental Example 2: Evaluation of high-temperature battery life characteristics The positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were mixed with a conductive material (acetylene black) and a PVdF binder in a weight ratio of 97.5:1.0:1.5 in N-methylpyrrolidone to prepare positive electrode slurries. The positive electrode slurries were applied to one side of an aluminum current collector, which was then dried and rolled to prepare positive electrodes.
[0105] Specifically, the negative electrode active material (a mixture of natural graphite and artificial graphite in a weight ratio of 50:50), SBR binder (M37, LG Chem), and conductive material (acetylene black) were added to the solvent water in a weight ratio of 96.0:3.0:1.0 to prepare a negative electrode slurry (solid content: 60% by weight). The negative electrode slurry was applied to a copper thin film as a negative electrode current collector, which was then dried and rolled to prepare a negative electrode.
[0106] A 15μm-thick polyethylene separator was interposed between the positive and negative electrodes to prepare an electrode assembly, which was then inserted into a battery case and an electrolyte was injected to prepare a lithium secondary battery. The electrolyte used was a solution of 1M LiPF6 dissolved in an organic solvent made of ethylene carbonate (EC): ethyl methyl carbonate (EMC) mixed in a volume ratio of 1:2.
[0107] The lithium secondary battery prepared as above was charged at 45° C. at 0.3 C to 4.25 V and discharged at 0.3 C to 2.5 V as one cycle, and the DCIR increase and capacity retention were measured while performing 100 charge and discharge cycles. The measurement results are shown in Table 4 below.
[0108] At this time, the resistance increase rate and the capacity retention rate were calculated using the following formulas 1 and 2.
[0109] Equation 1: Resistance increase rate (%) = {(resistance after 100 cycles / resistance after 1 cycle) x 100} - 100 Equation 2: Capacity retention rate (%) = (discharge capacity after 100 cycles / discharge capacity after 1 cycle) x 100
[0110] [Table 4]
[0111] From the results of Table 4, it can be confirmed that the cathode materials of Examples 1 to 4, in which the ratio of the cation mixing ratio of the large particle size cathode active material to the cation mixing ratio of the small particle size cathode active material (Ml / Ms) is between 0.6 and 4.0, and the ratio of the average particle size of the primary particles of the large particle size cathode active material to the average particle size of the primary particles of the small particle size cathode active material (Pl / Ps) is between 0.1 and 2.0, have little particle cracking due to rolling and have excellent life at high temperatures. On the other hand, it can be confirmed that the cathode material of Comparative Example 1, in which the Pl / Ps value satisfies the range of the present invention but the Ml / Ms value is less than 0.6, has little particle cracking, but the capacity retention rate and resistance increase rate at high temperatures are not as good as those of the Examples, and it can be confirmed that the cathode material of Comparative Example 4, in which the Ml / Ms value exceeds 4.0, has severe particle cracking, a poor capacity retention rate at high temperatures, and a poor level of resistance increase rate.
[0112] In addition, it was confirmed that the positive electrode material of Comparative Example 2, in which the Ml / Ms value satisfies the range of the present invention but the Pl / Ps value exceeds 2.0, exhibited particle cracking and poor high-temperature performance compared to the Examples, and it was found that Comparative Example 5, in which the Pl / Ps value was less than 0.1, exhibited not only particle cracking but also poor high-temperature life characteristics (capacity retention rate) and output characteristics (resistance increase rate) compared to the Examples.
[0113] Furthermore, it can be seen that the most degraded characteristics were observed in Comparative Example 3, in which both the Ml / Ms and Pl / Ps values were outside the range of the present invention.
Claims
1. comprising a large particle size positive electrode active material and a small particle size positive electrode active material, The large particle size positive electrode active material and the small particle size positive electrode active material each independently contain a lithium nickel-based oxide, When the cation mixing ratio of the large particle diameter positive electrode active material is Ml and the cation mixing ratio of the small particle diameter positive electrode active material is Ms, Ml / Ms is 0.6 to 4.0, A positive electrode material for a lithium secondary battery, wherein Pl / Ps is 0.1 to 2.0, where Pl is an average particle size of primary particles of the large particle size positive electrode active material and Ps is an average particle size of primary particles of the small particle size positive electrode active material.
2. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the large particle diameter positive electrode active material has a D50 of 8 μm to 18 μm.
3. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the small particle diameter positive electrode active material has a D50 of 2 μm to 7 μm.
4. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the large particle size positive electrode active material and the small particle size positive electrode active material are each independently composed of a single particle composed of a primary particle; a secondary particle composed of an aggregate of a number of primary particles; or a combination thereof.
5. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the average particle size of the primary particles of the large particle size positive electrode active material is 0.2 μm to 1.0 μm.
6. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the average particle size of the primary particles of the small particle size positive electrode active material is 0.5 μm to 2.0 μm.
7. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein Bl / Bs is 0.15 to 1.6, where Bl is the specific surface area of the large particle diameter positive electrode active material and Bs is the specific surface area of the small particle diameter positive electrode active material.
8. The positive electrode material for a lithium secondary battery according to claim 1, wherein the large particle diameter positive electrode active material and the small particle diameter positive electrode active material each contain a lithium nickel-based oxide represented by the following chemical formula 1: [Chemical formula 1] Li 1+x (N a Co b Mn c M d )O 2-y In the above Chemical Formula 1, M is at least one selected from the group consisting of Al, Mg, V, Ti, Zr, Nb, and W; x, a, b, c, and d are -0.10≦x≦0.20, 0.50≦a<1.0, 0<b≦0.40, 0<c≦0.30, 0≦d≦0.05, a+b+c+d=1, and 0≦y≦0.05, respectively.
9. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the large particle size positive electrode active material and the small particle size positive electrode active material each contain a lithium nickel-based oxide in which the molar ratio of nickel among transition metals is 70 mol % or more.
10. 2. The positive electrode material for a lithium secondary battery according to claim 1, comprising the large particle size positive electrode active material and the small particle size positive electrode active material in a weight ratio of 50:50 to 90:
10.
11. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the large particle size positive electrode active material has a cation mixing ratio of 1.0 at % to 2.0 at %.
12. 2. The positive electrode material for lithium secondary batteries according to claim 1, wherein the small particle size positive electrode active material has a cation mixing ratio of 0.5 at % to 1.5 at %.
13. A positive electrode for a lithium secondary battery comprising the positive electrode material for a lithium secondary battery according to any one of claims 1 to 12.
14. A lithium secondary battery comprising the positive electrode for lithium secondary batteries according to claim 13.
Citation Information
Patent Citations
Positive electrode active material for lithium secondary battery, method of preparing the same and lithium secondary battery including the same
JP2020072091A
Test apparatus of elevator
KR102005732B1
Cover apparatus for heater pipe
KR102850770B1
Positive electrode active material and battery comprising same
WO2020049793A1
Positive electrode material for secondary battery and lithium secondary battery comprising the same
KR1020210031325A